Konstytucyjny model pieczy nad zawodami zaufania publicznego - Świderski, Krzysztof (Studia Prawa Publicznego, 2024)
The article presents selected problems concerning custody for persons with professions of public trust. First, attention is drawn to the historical understanding of custody. In the past, custody was perceived as a manifestation of managing administration. The current way of thinking about custody results from the custody model contained in Art. 17 section 1 of the Constitution of the Republic of Poland. Exercising custody is one of the forms of coercive professional self-governing body activity. Custody is exercised by an entity endowed with administrative power, which is a component of public authorities. The purpose of custody is to protect the public interest, understood primarily as building public trust. The basic factors that build public trust are high professionalism of services, the obligation to maintain professional secrecy, and providing citizens with full information about the service provided. Activities undertaken as part of the exercise of custody serve the purpose of enhancing and protecting public trust. Custody is exercised with regard to persons performing professions of public trust. Such persons remain outside the public administration and perform professional activities on their own account and in their own name. These are private individuals that render specialized services which are important from the point of view of the basic goods of an individual, such as health, property interests or personal rights. Administrative custody is exercised to ensure that the needs of citizens are properly met. The competent professional self-government bodies should ensure the conditions for providing citizens with the best quality services in the field of health care, legal protection, property protection and wherever public safety is concerned. Exercising custody by professional self-governments makes it possible to interfere with authority in socially important activities undertaken by persons outside the structures of public administration.